Analisis Kualitas Website SMKN Terhadap Kepuasan Pengguna Menggunakan Metode Webqual 4.0 - Falencia, Feiren; Purnama, Benni; Mulyono, Herry (TIN: Terapan Informatika Nusantara, 2024)
Based on observation to total visitor of website SMKN 2 Kota Jambi from June – September 2022 obtained result that total visitor is decrease, which total visitor on September is 1.680 people. Therefore this research is needed to analyze and looking for magnitude influence website quality of SMKN 2 Kota Jambi to user satisfaction use Webqual 4.0 method and IBM SPSS Statistic 26 as application for analyze data statistic with total sample 345 respondents. Based on test that consists validity test, reliability test, multicollinearity test, heteroscedasticity test and multiple linear regression analysis, that obtained research result is all indicator comply valid and reliable category and there is no multicollinearity and heteroscedasticity. For multiple linear regression analysis through t-test and f-test that results is all independent variables (usability quality, information quality and interaction quality) positive and significant effect partially and simultaneously to dependent variable (user satisfaction) with interaction quality as variable that has highest influence to user satisfaction, then through determination coefficient analysis obtained the value of R Square is 59,3% that means independent variables influence to dependent variable is good.